2017
DOI: 10.1111/jocn.13637
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anxiety and depression among patients with implantable cardioverter defibrillator

Abstract: The study findings direct the care to improve health-related quality of life by reducing and controlling vulnerabilities arising from depression. Patients who are older people (≥aged 60) and more self-care dependent perceive higher depression. Nursing strategies are suggested to reduce depression especially for those who are older people and more self-care dependent. Early screening is essential to provide immediate care for reducing vulnerabilities arising from depression. Performing comprehensive assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
0
8
0
5
Order By: Relevance
“…These variables were selected based on literature. 25 28 To assess the effects of Type D personality (high NA/high SI) on health status, three dummy variables were created: high NA/low SI, low NA/high SI, and low NA/low SI. Low NA/low SI served as the reference category.…”
Section: Methodsmentioning
confidence: 99%
“…These variables were selected based on literature. 25 28 To assess the effects of Type D personality (high NA/high SI) on health status, three dummy variables were created: high NA/low SI, low NA/high SI, and low NA/low SI. Low NA/low SI served as the reference category.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work examining ICD implantation in individuals with coronary artery disease found no association between education level and worse psychological functioning [37,38]. Wong et al [39] found an association between low education level and worse depression scores, but reported no association with anxiety. It is important to note however, that many studies have not included education level in their analyses [18-22].…”
Section: Discussionmentioning
confidence: 99%
“…El tiempo desde el implante del cardiodesfibrilador fue de 15,98 meses (DE=±9), con un rango de 1-35 meses, aunque los hallazgos de otros autores arrojaron una media de 2,54 años (DE=±1,43) (8) , 3,65 años (DE=±3,4) (38) , 4,4 años (DE=±3,8) (18) , 4,7 años (DE=±3,9) (22,21,33) , 5,3 años (DE=±3,7) (24,25) y 5,7 (DE=4,1) (32) demostrando mayor tiempo transcurrido desde la inserción del dispositivo.…”
Section: Discussionunclassified
“…Por otra parte, se observó que el 24,7% de los participantes habían experimentado descargas del dispositivo, resultados similares a los obtenidos en una investigación de Dinamarca con un 24% (37) . Los valores difieren de los resultados en Suecia, España, Australia, Estados Unidos y Brasil, cuyos porcentaje de usuarios con historiales de descarga fueron superiores al 35% pero inferiores al 50% (16,19,21,22,(31)(32)(33) , y del mismo modo, en algunos países europeos y asiáticos donde menos del 14% de participantes experimentaron descargas (15,26,28,38) . Esto muestra una variabilidad del historial de descargas en los participantes de diferentes estudios.…”
Section: Discussionunclassified
See 1 more Smart Citation